2022
DOI: 10.3390/pathogens11101187
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Outcomes in Children with Congenital Toxoplasmosis—A Systematic Review

Abstract: Even in the absence of manifestations at birth, children with congenital toxoplasmosis (CT) may develop serious long-term sequelae later in life. This systematic review aims to present the current state of knowledge to base an informed decision on how to optimally manage these pregnancies and children. For this, a systematic literature search was performed on 28th July 2022 in PubMed, CENTRAL, ClinicalTrials.gov, Google Scholar and Scopus to identify all prospective and retrospective studies on congenital toxo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 108 publications
0
5
0
2
Order By: Relevance
“…Previous studies have shown that most asymptomatic infected children develop clinical symptoms. 31 , 32 Neonatal tests can frequently reveal lesions; however, standard well-child examinations frequently miss congenital toxoplasmosis. Congenital toxoplasmosis monitoring requirements and clinical toxoplasmosis management strategies are still debatable, largely because of the lack of comprehensive information on the nature of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that most asymptomatic infected children develop clinical symptoms. 31 , 32 Neonatal tests can frequently reveal lesions; however, standard well-child examinations frequently miss congenital toxoplasmosis. Congenital toxoplasmosis monitoring requirements and clinical toxoplasmosis management strategies are still debatable, largely because of the lack of comprehensive information on the nature of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…Las infecciones fetales del primer trimestre tienen mayor probabilidad de terminar en aborto; así, las infecciones entre las semanas 12-24, pueden llevar a hidrocefalia grave. En cambio, las que ocurren en las semanas 30-39, llevan a infecciones asintomáticas al nacer, con riesgo de desarrollar lesiones oculares más adelante 26 . La historia natural de niños que se examinaron luego del nacimiento en Colombia y que no tuvieron tratamiento prenatal, muestra que 41% nacieron con hepato-esplenomeglia, 30% con compromiso ocular y 36% con compromiso neurológico 27 .…”
Section: Toxoplasmosis Gestacional Y Fetalunclassified
“…In immunocompromised individuals, the infection could have life-threatening sequels, such as toxoplasmic encephalitis, myocarditis, or disseminated infections [7,8]. Congenital toxoplasmosis is also a life-threatening condition which may lead to abortion, stillbirth, and preterm birth [9][10][11][12]. The intensity of T. gondii infection depends on several factors, including genetic background [13], immunity status [14], and the parasite virulence [15,16].…”
Section: Introductionmentioning
confidence: 99%